Numerical investigation of surface and volume thermal imaging of nickel-graphene foam sheets by finite element method - Nouf K. AL-Saleem; Taher Ghrib; Aishah AL-Naghmaish; Nabil Gmati; Anis Mohamed; Noureddine Sfina; Ghada I. Ameereh (Results in Engineering)
The detailed theoretical analysis of heat equations is applied to Nickel foam specimens with various pore-size coated graphene thin film of 200 nm thickness under laser excitation. 2D and 3D thermal numerical models were proposed by applying the finite element method. To explain the proposed numerical model, the influence of discretization parameters and the heat diffusion length were studied. The proposed model accurately predicts the thermal spreading in the specimens. The numerical model showed the sensitivity of the model for the structure variation to achieve an accurate thermal imaging when the used laser is of radius value is within of specimen pore size and modulated at low frequency.